Evaluation of macula ganglion cell analysis and retinal nerve fiber layer thickness in preperimetric glaucoma, early stage glaucoma and healthy individuals - Ozlem AKTAS OZALTUN; Ozlem GURBUZ KOZ; Ahmet Alper YARANGUMELI (Photodiagnosis and Photodynamic Therapy, 2025)
Purpose: In this study, it was planned to compare the macular ganglion cell analysis (GCA) and peripapillary retinal nerve fiber layer (pRNFL) of the patients with preperimetric glaucoma (PPG), early stage glaucoma (EG) and the control group. Methods: This retrospective study included a total of 103 eyes: 38 from EG patients, 30 from PPG patients, and 35 from healthy individuals at Ankara Bilkent City Hospital Glaucoma Unit between January 2018 and September 2021. Eyes were categorized into control, PPG, and EG groups based on visual field (VF) classification. Topcon DRI Optical Coherence Tomography (OCT)-1, a Swept−Source OCT (SS-OCT), measured optic nerve head parameters, pRNFL, gangliyon cell inner plexiform layer (GCIPL), and ganglion cell complex (GCC) thickness. Glaucomatous defects were identified using also the SS-OCT SuperPixel map. Diagnostic efficacy of OCT parameters was assessed through area under the curve (AUC) values. Results: All pRNFL and ganglion cell parameters in OCT showed significant differences between the control-PPG and control-EG groups (p < 0.05). GCIPL, GCC, and pRNFL thicknesses in the PPG and EG groups were significantly lower than those in the control group (p < 0.05). The mean pRNFL thickness emerged as the most valuable diagnostic parameter for distinguishing between the control and EG groups (p < 0.05). In the wide-field SuperPixel map, the frequency of glaucomatous defect detection was higher in the EG group than in the PPG group (p < 0.05). Mean pRNFL and mean GCIPL thicknesses exhibited the highest sensitivity and specificity for differentiating glaucoma groups from controls. Conclusion: OCT parameters were not significantly superior to each other in control-PPG and control-EG. The evaluation of pRNFL and GCA together is still considered to be the most valid diagnostic method.